Internet governance: present situation of Bangladesh and Malaysia - Islam, Md. Zahidul; Anzum, Rabeya (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Internet is a very well-known word in this world sinceit has a revolutionary impact on our society. Nowadays we cannot think about our daily life without using internet and speciallysocial media is solely connected to it. Mass media has become more powerful in terms of spreading any news throughout the globe. With the help of social media we can attainalmost every information about the happenings of the world.At the same time, it has become very easy to create confusion among peopleby manipulating information and spreading it among people.Authorites has come forward tosuppress this kind of adversepactice of social media and imposed some regulations locallyas well as internationally. The aim of this paper is to focus on legal aspects of internet governance and the ongoing situation in terms of accessing social media in Bangladesh and Malaysia. It is qualitative research work.The information entitled in this paper has been extracted from various newspapers, articles, books and statutes. The Government of Malaysia and Bangladesh has adopted some Acts, Rules, and Regulations to avoid the malpractice of misusing Internet.